IMPLEMENTASI FUZZY TAHANI DALAM MENENTUKAN PEMILIHAN MOTOR HONDA PADA PD. UTAMA MOTOR MENGGUNAKAN VISUAL BASIC 6.0 - Mesterjon Mesterjon; Galih Putra Kusuma (Jurnal Media Infotama, 2011)
This study was conducted on February 28, 2013 until March 28 to PD 201. Main Motor Bengkulu city in order to make the application of Fuzzy Implementation Tahani In Determining Honda Motor Selection by Using Visual Basic 6.0 mainly determine the price variable motors, an empty weight of the motor, the motor length, the width of the motor, the motor height, capacity moto, motor torque, the motor volume . using Visual Basic 6.0. Based on the results of the study showed that it takes a simple application program in order to facilitate visitors to determine or select the appropriate motor criteria. application made in visual basic 6.0 programs can easily recommend the results consumers wantKeywords: Fuzzy Implementation